STUDI INTEGRASI PENGEMBANGAN AGROINDUSTRI DAN AGROWISATA DI DAERAH ALIRAN SUNGAI (DAS) KALI BEKASI, KABUPATEN BOGOR - Am Fauzi, Djamudin (JURNAL PERTANIAN, 2012)
Efforts to increase the value added of agricultural products through the integration of sustainabledevelopment of agro-industry and agro-tourism is considered very strategic. Done through theintegration planning analysis by determining the location of the selected areas upstream Kali Bekasiwatershed with value 358 and Top- upstream Kali Bekasi watershed with value 365. Based BogorDistrict government policy is an area of ecotourism, urban agriculture and industry as well as barns.Determination of selected commodities of rice, cassava, bamboo, banana and coffee, as well asagroindustry products selected rice flour, tapioca flour, bamboo furniture, banana chips and coffeepowder. An excellent potential for commodity and commodity groups farm field Bogor District In2011. Types of attractions that can be displayed consists of one kind of attraction cultivation, twotypes of attraction picking/harvesting and laboratories as well as three types of attraction productprocessing/agro-industry and the type of supporting attractions. Analysis of simulation andoptimization of agro products with the kind of tourist attraction demonstrated added value ofoptimization. 18. 677. 500 rupiah. Based on the analysis of the feasibility of the integration of thedevelopment investment resulting NPV of 9,428,040,717 rupiah. IRR of 40%, Net B/C of 2.27, andPBP 3 years 4 months 12 days with BEP for 1.56.554.139 rupiah. The results of the analysis theintegrated of agroindustry and agrotourism development may increase the potential value added byrequiring the involvement of relevant stakeholders, ie farmers actors, agroindustry actors,agrotourism actors, financial institutions/investors and the communities around the area and thesupport of government policy, both as a facilitator and a catalyst. The purpose of the research, is theintegrated of agroindustry and agrotourism of sustainable development. The research method usingAHP, MPE, linear programming and financial analysis criteria such as NPV, IRR Net B/C, PBP andBEP.